Free and bound aromatic components of Loureiro and Alvarinho grape varieties from the vinhos verdes region - Oliveira, J. M. (2000)
Free and glycosidically bound volatiles were quantified in five grape samples grown in 1996 from two of the most important Vitis vinifera varieties of Vinhos Verdes Region, Loureiro and Alvarinho. The most recommended sub-region for monovarietal wine production and an alternative sub-region were chosen. A third sample of Alvarinho was selected from a different and particular pebble soil. Forty compounds in the free fraction and sixty-four in the glycosidically bound fraction including alcohols, monoterpenic compounds, C13 norisoprenoids, phenols, C6 compounds and carbonyl compounds were quantified in the samples of the two varieties. The results showed that these two Portuguese varieties were quite different regarding the varietal flavour compounds, even grown in the different sub-regions. Samples of Loureiro variety showed higher content of free monoterpenic compounds than Alvarinho, mainly linalool, pyran linalool oxides and 3,7-dimethylocta-1,7-dien-3,6-diol. Free linalool seemed to be characteristic of Loureiro variety, with levels higher than its perception threshold. Both cultivars contained important levels of bound monoterpenic compounds and C13 norisoprenoids, bound linalool occurring in high levels in both varieties. Nevertheless, Alvarinho variety contained higher amounts of bound geraniol and monoterpenic oxides and diols, mainly trans-pyran linalool oxide, geranic acid and (Z)-8-hydroxylinalool, while Loureiro variety was richer in bound α-terpineol and p-1-menthen-7,8-diol.